The Effect of Implementing Skin to Skin Contact on the Increase in Body Temperature of Newborn Babies with Premature - Jamil, Maria Ulfah; Amalia, Novianti Rizki; Mulyana, Asep (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: Infant Mortality Rate (IMR) is a benchmark used to determine the level of health development and quality of life in a country. The occurrence of prematurity in pregnancy is caused by multiple factors: maternal factors, fetal factors, and other factors. Premature birth causes the organs of the body to not be able to function perfectly, so that the adjustment of organ function to changes in conditions from intrauterine to extrauterine is very difficult for the baby. Changes in extrauterine conditions can cause stress in premature babies. The mechanism of heat loss through evaporation is the loss of body heat through the air. Preventive efforts by midwives can prevent the risk of hypothermia in newborns with the skin-to-skin method between mother and baby, provide early initiation of breastfeeding and immediately swaddle the baby. Objective: The aim of this study was to determine the effect of skin to skin contact on increasing the body temperature of premature newborns. Method: The method used in this study is to use the PreExperiment design with One group pre-test–post-test design. The sample in this study was non-probability sampling with inclusion and exclusion criteria of 14 premature babies. Result: The results of this study show that there is an influence of skin to skin implementation on increasing the body temperature of premature newborns at Jasa Kartini Hospital, P-Value 0.000 < 0.05. Conclusion: Based on the research results obtained, there is an influence of the implementation of skin to skin contact on increasing the body temperature of premature newborns.